2013
DOI: 10.6002/ect.2012.0053
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Bone Marrow Mesenchymal Stem Cell Therapy in the Subacute Stage of Traumatic Brain Injury by Lumbar Puncture

Abstract: Objectives: To explore the clinical therapeutic effects and safety of autologous bone marrow mesenchymal stem cell therapy for traumatic brain injury by lumbar puncture. Materials and Methods: A total of 97 patients (24 with persistent vegetative state and 73 with disturbance motor activity) who developed a complex cerebral lesion after traumatic brain injury received autologous bone marrow mesenchymal stem cell therapy voluntarily. The stem cells were isolated from the bone marrow of the patients and transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 36 publications
(32 reference statements)
1
74
0
2
Order By: Relevance
“…We must also understand these cells' mechanisms of interaction and how we can use these mechanisms to achieve full regeneration. Based on the studies cited here, it is possible to affirm that in the near future we will have effective therapies against various diseases that affect and challenge the medical community and the population [53] 2013 20 22-54 yr MSCs -6 mo García-Santos et al [54] 2013 11 33-61 yr MSCs -12 mo Tian et al [55] [20] 2012 31 10-50 yr BMCs -33 mo Martínez et al [57] 2012 67 49.2 ± 10.3 1 yr CD133+ -12 mo Mazzini et al [28] 2012 19 20-75 yr MSCs -108 mo Moviglia et al [47] 2012 7 33-78 yr NSCs T-cell vaccine 12 mo Prasad et al [58] 2012 11 30-70 yr MNCs -52 wk Brazzini et al [59] 2010 53 38-81 yr BMCs -1-18 mo Karussis et al [26] 2010 19 53.0 1 yr MSCs -25 mo Lee et al [60] 2010 16 64.0 ± 11.6 1 yr MSCs -5 yr Venkataramana et al [61] …”
Section: Resultsmentioning
confidence: 99%
“…We must also understand these cells' mechanisms of interaction and how we can use these mechanisms to achieve full regeneration. Based on the studies cited here, it is possible to affirm that in the near future we will have effective therapies against various diseases that affect and challenge the medical community and the population [53] 2013 20 22-54 yr MSCs -6 mo García-Santos et al [54] 2013 11 33-61 yr MSCs -12 mo Tian et al [55] [20] 2012 31 10-50 yr BMCs -33 mo Martínez et al [57] 2012 67 49.2 ± 10.3 1 yr CD133+ -12 mo Mazzini et al [28] 2012 19 20-75 yr MSCs -108 mo Moviglia et al [47] 2012 7 33-78 yr NSCs T-cell vaccine 12 mo Prasad et al [58] 2012 11 30-70 yr MNCs -52 wk Brazzini et al [59] 2010 53 38-81 yr BMCs -1-18 mo Karussis et al [26] 2010 19 53.0 1 yr MSCs -25 mo Lee et al [60] 2010 16 64.0 ± 11.6 1 yr MSCs -5 yr Venkataramana et al [61] …”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that neurons differentiated from MSCs exhibit functional (9). Compared with the other cell types, autologous BMMSCs avoid ethical controversy and immune rejection, and can be easily obtained through repeated harvests (7). Hence, BMMSCs has become an important source of seed cells for the treatment of a wide variety of nervous diseases.…”
Section: Discussionmentioning
confidence: 99%
“…TBI always destroy neurons, glial cells, nerve fibers and blood vessels directly, and the effective treatment of neurological impairment has been a widespread problem in clinical practice (7). Early studies suggested that the CNS had no ability to renew or regenerate after injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[96][97][98][99] Several clinical trials in cell-based treatment for TBI recovery have demonstrated safety of this therapeutic approach. 100,101 However, the administration route, dose, and time window still remain controversial.…”
Section: Neurorestorationmentioning
confidence: 99%